2003
DOI: 10.1207/s15327663jcp13-1&2_15
|View full text |Cite
|
Sign up to set email alerts
|

Shoppers in Cyberspace: Are They From Venus or Mars and Does It Matter?

Abstract: Requests for reprints should be addressed to ~~b~ Dholakia, nology but have not yet settled into domestic roles, to see if College of Business Administration, University of Rhode Island, 7 Lippitt such Stereotypes exist. First the literature on gender, shop-Road, Kingston, RI 022814802, E-mail: mby @uri.edu ping, and technology is reviewed. Then an empirical study to Accepted by Dawn Iacobucci

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…5,33 Several explanations have been advanced in the literature for the gender differences including risk perception, 34 a general attitude towards technology 35 and differences in role specializations. 36,37 Perhaps, the most widely investigated reason is that women appear to be more concerned with risk associated with e-commerce than their men counterparts. 11,38,39 This explanation is consistent with the earlier studies which found women were also more risk averse in other domains including medical, environmental and fi nancial matters.…”
Section: Literature Review and Hypotheses Development Demographic Detmentioning
confidence: 99%
“…5,33 Several explanations have been advanced in the literature for the gender differences including risk perception, 34 a general attitude towards technology 35 and differences in role specializations. 36,37 Perhaps, the most widely investigated reason is that women appear to be more concerned with risk associated with e-commerce than their men counterparts. 11,38,39 This explanation is consistent with the earlier studies which found women were also more risk averse in other domains including medical, environmental and fi nancial matters.…”
Section: Literature Review and Hypotheses Development Demographic Detmentioning
confidence: 99%
“…Therefore, we have drawn from traditional retailing literature to conceptualise our arguments on how gender roles will have an influence on permission. Indeed, recent research in retailing has begun to present typologies o f t h e r e s p e c t i v e s h o p p i n g s t y l e s o f m e n a n d w o m e n ( B a k e w e l l a n d M i t c h e l l , 2 0 0 4 ; Campbell, 1997;Dholakia and Chiang, 2003;Miller, 1998;Otnes and McGrath, 2001). …”
Section: The Role Of Gendermentioning
confidence: 99%
“…Indeed, recent research has begun to present typologies of the respective shopping styles of men and women [Allegra, 2002;Bakewell and Mitchell, 2004;Campbell, 1997;Dholakia and Chiang, 2003;Miller, 1998;Otnes and McGrath, 2001;Underhill, 1999]. However, despite this work, there remains a need for further research examining differences in shopping behaviour across gender [Otnes and McGrath, 2001].…”
Section: The Influence Of Gendermentioning
confidence: 99%